Novel Thermotolerant and Flexible Polyimide Aerogel Separator Achieving Advanced Lithium‐Ion Batteries. (8th October 2021) - Deng, Yurui; Pan, Yuelei; Zhang, Zhongxin; Fu, Yangyang; Gong, Lunlun; Liu, Chengyuan; Yang, Jiuzhong; Zhang, Heping; Cheng, Xudong
Abstract: Separators are vital parts of all lithium‐ion batteries (LIBs), and they play a critical role in their thermal safety and electrochemical performance. Considering the low thermal stability and inferior electrolyte wettability of commercial polyolefin membranes, in this study, a novel thermotolerant polyimide aerogel (PIA) separator is designed. This is the first report on the use of chemically cross‐linked PIA separators for LIBs. The outstanding porosity (78.35%) and electrolyte absorption (321.66%) of PIA separators contribute to the low internal resistance and outstanding electrochemical performance of LIBs, which can retain a high specific capacity of 118 mAh g −1 after 1000 cycles at a current density of 1 C. In addition, The LiFePO4 |Li metal batteries with PIA separators are extremely stable at 90 °C (>300 cycles), and maintain stability even at 120 °C. More importantly, for pouch batteries, PIA separators result in higher thermal runaway temperatures compared with Celgard separators. In this paper, the pyrolysis mechanism and thermodynamic process of PIA separators are clarified by DFT calculations and in situ synchrotron vacuum UV photoionization mass spectrometry experiments. Abstract : A novel thermotolerant polyimide aerogel separator is prepared and its pyrolysis mechanism is clarified through in situ synchrotron vacuum UV photoionization mass spectrometry experiments and DFT calculations. Benefiting from its high porosity and thermal stability, the prepared separator can help to achieve the outstanding electrochemical performance of the used battery and improve the thermal safety of LIBs.